Techniques for adjusting qualities of aircraft structural models for more effective aeroelastic flutter analyses - Olejnik, Aleksander; Kachel, Stanislaw; Rogólski, Robert (Journal of physics. Conference series, 2023)
To solve numerically the problem of aeroelastic flutter, two virtual components are required: a structural finite element model (FEM) and an aerodynamic model. MSC Software package containing Nastran with embedded flutter solution enables to perform calculations with the use of an integrated aeroelastic model. For data block including the model and the set of entry parameters, flutter equation is being solved. On the basis of postprocessed output data curves of run for resulting parameters can be plotted which gives information of flutter critical point. Numerical results may be subject to some uncertainty. Result deviation could occur as effects of various factors resulting from inaccurate geometry or poor structural qualities of mapped aircraft. Structural defects affecting mass or stiffness matrices of FEM are often hard to identify. Aspects important for effective flutter solutions are strictly connected with the coincidence of structural properties of the real aircraft and its model. In the paper, the method of numerical flutter analysis was presented with the use of techniques available in MSC Nastran. Three assessment methods were proposed to identify structural parameters usable for validating FEMs. The method of mass correction relies on adjustment of model mass values and tuning the location of the center of mass of the model to the coordinates of the location of the center of mass of the real aircraft. For adjusting stiffness of model parts, very useful are results obtained from strength test of the real airframe. The completely reliable but costly method is performing ground vibration tests (GVT) to measure precisely resonant frequencies and natural modes of free vibrations. The results obtained from experiments should be treated as the referenced, but tuning FEM to them requires both adjusting numerical eigenfrequencies and normal modes.